2011
DOI: 10.1002/jbm.b.31902
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dentin substrates to simplify wet‐bonding: A leakage‐free and reliable tensile strength interface for long‐lasting restorations

Abstract: The wet-bonding procedure can be simplified by eliminating the primer. An aqueous mixture of 1% citric acid and 1% ferric chloride (1-1) was hypothesized as providing an easier dehydratable thinner substrate to which 4-META/MMA-TBB resin can adhere reliably. The 1-1 was applied for 10 s and rinsed off with water for 10 s. Demineralized dentin under four conditions was prepared before bonding to PMMA rod using 4-META/MMA-TBB resin: air-dried 10 s (D-NP); air-dried 10 s, primed 60 s with 5% 4-META in acetone (D-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
0
6
0
1
Order By: Relevance
“…The critical difference in chemical composition between PMMA-TBB and PMMA-BPO materials is the polymerization initiator. Resin materials containing TBB as a polymerization initiator are widely used as cementing materials in dentistry [ 18 , 50 , 51 , 52 , 53 ], because of the higher degree of polymerization [ 54 ]. Another unique feature of TBB-containing cements is that the polymerization reaction proceeds effectively in a humidified environment [ 17 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…The critical difference in chemical composition between PMMA-TBB and PMMA-BPO materials is the polymerization initiator. Resin materials containing TBB as a polymerization initiator are widely used as cementing materials in dentistry [ 18 , 50 , 51 , 52 , 53 ], because of the higher degree of polymerization [ 54 ]. Another unique feature of TBB-containing cements is that the polymerization reaction proceeds effectively in a humidified environment [ 17 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…A 1–3 µm hybridized dentin layer suggested that 1-1 conditioned dentin was sufficiently permeable for water to evaporate and for monomers to impregnate. Thus, only blot-drying with or without primer (primerless-wet bonding) can produce a complete hybrid layer that reinforces the dentin [ 10 , 17 ] and prevents dye penetration of direct restorations [ 7 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…A morfologia da área de união encontrada com o uso da mistura de ácido cítrico e cloreto férrico (solução 10:3) está de acordo com os relatos da literatura Piemjai et al, 2011). A capacidade de formação de uma zona de hibridização sobre dentina tratada com solução 10:3 já é conhecida há muito tempo.…”
Section: Discussionunclassified